LOGICAL AND METHODOLOGICAL MEASUREMENTS OF THE IDEAL’S NATURE - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article on the materialist philosophy's basis reveals the ideal's dialectics, the logical and methodological problems in studying of this phenomenon.